Analysis of the profile of self-inflicted violence in Santa Catarina in 2023 (Research, Society and Development, 2025)
Introduction: Self-harm is the violence that a person inflicts on him/herself, which can be suicide or self-mutilation. This behavior is complex and results from psychosocial, emotional, gender, and sociocultural factors. Objective: To discuss the profile of self-harm in the state of Santa Catarina in 2023. Methods: Observational study with an ecological design on self-harm in Santa Catarina in 2023, based on data collected from the DataSUS database. Results: In 2023, Santa Catarina recorded 9,858 cases of self-harm (rate of 134 per 100,000 inhabitants), with a higher incidence in the age group of 20 to 29 years (28.53%), especially among women (68.36%). Hangings occurred at a rate of 11 per 100,000 inhabitants, with a predominance of males (59.19%) and a higher incidence in the 20-29 age group (26.65%). The use of sharp objects occurred in 25 cases per 100,000 inhabitants, with 70.03% of women and a higher incidence also in the 20-29 age group (27.31%). Poisonings accounted for 6,178 cases (84 per 100,000 inhabitants), with a predominance among women (73.46%). There were 49 cases involving firearms, with a rate of 0.66, and a predominance of males (81.63%). Conclusion: The analysis of self-harm in Santa Catarina in 2023 highlights the high incidence of self-harm among young adults, especially women. The methods used, such as hanging and poisoning, reflect both accessibility and the psychological factors involved.